2015
DOI: 10.5140/jass.2015.32.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating High-Degree-and-Order Gravitational Harmonics and its Application to the State Predictions of a Lunar Orbiting Satellite

Abstract: In this work, an efficient method with which to evaluate the high-degree-and-order gravitational harmonics of the nonsphericity of a central body is described and applied to state predictions of a lunar orbiter. Unlike the work of Song et al. (2010), which used a conventional computation method to process gravitational harmonic coefficients, the current work adapted a well-known recursion formula that directly uses fully normalized associated Legendre functions to compute the acceleration due to the non-spheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Song et al (2010a) reported that the lifetime of a lunar polar orbiter is significantly affected by the different degrees and orders of the lunar gravity model, by gravitational attractions of a third body (specifically the Earth), and by the different orbital inclinations. This software was later updated by Song & Kim (2015) by applying a well-known recursion formula that directly uses fully normalized associated Legendre functions to compute the acceleration because of the non-sphericity of the moon. By implementing this formula, a significant amount of computation time was saved, even with high-degree-andorder harmonic coefficients, and accuracy degradation that can arise during numerical simulations, was prevented (Song & Kim 2015).…”
Section: Past Efforts: Starting With Mars Mission Trajectory Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al (2010a) reported that the lifetime of a lunar polar orbiter is significantly affected by the different degrees and orders of the lunar gravity model, by gravitational attractions of a third body (specifically the Earth), and by the different orbital inclinations. This software was later updated by Song & Kim (2015) by applying a well-known recursion formula that directly uses fully normalized associated Legendre functions to compute the acceleration because of the non-sphericity of the moon. By implementing this formula, a significant amount of computation time was saved, even with high-degree-andorder harmonic coefficients, and accuracy degradation that can arise during numerical simulations, was prevented (Song & Kim 2015).…”
Section: Past Efforts: Starting With Mars Mission Trajectory Designmentioning
confidence: 99%
“…This software was later updated by Song & Kim (2015) by applying a well-known recursion formula that directly uses fully normalized associated Legendre functions to compute the acceleration because of the non-sphericity of the moon. By implementing this formula, a significant amount of computation time was saved, even with high-degree-andorder harmonic coefficients, and accuracy degradation that can arise during numerical simulations, was prevented (Song & Kim 2015). To establish more realistic design concepts, the TLI maneuver was optimized and analyzed by applying a finite thrust model (Song et al 2010b).…”
Section: Past Efforts: Starting With Mars Mission Trajectory Designmentioning
confidence: 99%
“…More details regarding the force modeling method, for example, those related to implementation of the recursion algorithm and determination of the inertial acceleration due to the nonsphericity of the central body, expressed in body-fixed Cartesian coordinates, can be found in [54][55][56][57].…”
Section: Force Modelingmentioning
confidence: 99%
“…The initial orbital epoch is assumed to be January 01, 2020, 00:00:00 (UTC), corresponding to Korea's first experimental lunar orbiter mission, the launch and subsequent nominal mission of which are set to occur in approximately 2019∼ 2020. To numerically integrate the orbiter's states, the proven performance of KARI's lunar orbit propagator is used [57]. Note that external perturbing forces other than the force due to the lunar gravity field are not additionally considered to focus on the main objectives of the current study.…”
Section: Data and Assumptionsmentioning
confidence: 99%
“…To ensure the successful launch of the KPLO, KARI is now performing extensive trajectory design and analysis activities, including joint efforts between KARI and NASA to validate the trajectory design and navigation performance. Several preliminary design studies have already been conducted for lunar mission trajectory design and analysis (Song et al 2008;Song et al 2009;Song et al 2010;Woo et al 2010;Song et al 2011;Choi et al 2013;Song & Kim 2015) as well as orbit determination analysis Lee et al 2017). However, most of the previous work was mainly focused on the optimal trajectory generation from the nominal trajectory planning point of view.…”
Section: Introductionmentioning
confidence: 99%